Metode Penetapan Fatwa Dalam Membangun Perdamaian Perspektif Imam Ali goma (Studi Analisis Fiqh Tashabbuh Dengan Non Muslim): Metode Fatwa; Perdamaian; Imam Ali gomaa; Tasyabbuh - Nuruddien, Muhammad Nuruddien; Mahmoud Ismaeil Mohamed Mashal (Center for Research and Development of Religious Literature and Heritage, 2023)
In Islam, the issuance of a fatwa is a significant task that not everyone is equipped to do so, as it requires deep understanding of Islamic sciences, jurisprudence, and principles thereof. This study discusses the process of formulating a fatwa, particularly from Imam Ali Gomaa's perspective, emphasizing the importance of methodical approaches in fatwa creation. The paper uses a normative research approach, examining classical and contemporary texts and rulings. The study outlines a four-step fatwa issuance process: defining the issue, exploring its details, elucidating the legal ruling, and making the final decision. It highlights the need for fatwa producers to understand societal realities and connect them with religious texts, while ensuring moderation and balance. The paper also discusses nuances in judgments on acts resembling non-Muslim practices, stating they can range from being forbidden to commendable, depending on specific circumstances. For example, celebrating the Gregorian New Year is permissible, barring any religiously prohibited behaviors. This is despite objections from some factions, like the Madura scholars alliance, who view it as inappropriate resemblance with non-Muslim practices